Transforming Perspectives Through Virtual Exchange: A US-Egypt Partnership Part 2 - Collins, Sarah L.; Mueller, Savanah; Wood, Elizabeth A.; Stetten, Nichole E. (Frontiers in Public Health, 2022)
Collaborative online international learning programs, such as virtual exchange, that utilize telecollaborative activities have been integrated into more classrooms within the higher education setting. These programs provide students exposure to international cultures, perspectives, and ideas is no longer considered “value added”, but a prerequisite to entering many workforces. These programmatic objectives compliment Mezirow’s Transformative Learning Theory, that substantiates two major elements of transformative learning are critical reflection and dialectical discourse. This study presents the second half of a qualitative inquiry into the prominent themes that arose during a virtual exchange that was conducted in March 2021 between students in the United States (US) enrolled in a global public health course and Egyptian microbiology students. This study sought to expand upon the Transformative Learning Theory through inductive analysis procedures to offer a modernized adaptation of the theoretical framework within international learning environments. Student responses enrolled in an undergraduate global public health course were collected and analyzed by two coders using inductive/open coding to identify salient codes. These codes were then summarized into categories and subsequently defined. Resulting themes include Connectedness, Openness, Acquisition of Knowledge and Skills, Communication, Cultural Identity, Anticipation of Options for New Roles, Relationships, and Actions, and Absence of Change. Several themes have corresponding categories and subcategories. Adult learning environments such as the modern college classroom have changed with the introduction and reliance upon online learning domains, as well as the diversification of higher education student demographics, accentuating the need to inductively analyze student learning processes and outcomes. In doing so, our findings provide a modernized adaptation of the Transformative Learning Theory that allows for adult learning theorists, researchers, and scholars to integrate tenets of transformative learning more appropriately. As such, this provides an opportunity for educators to coalesce the identified mechanisms (e.g., openness, cultural background, anticipation of roles and relationships) to bolster student’s willingness and ability to engage in transformative critical reflections. By capitalizing on students’ innate characteristics, such as open-mindedness predispositions and cultural background, educators are able to augment transformative learning strategies through tailored assignments and course activities.